Escin, a Pentacyclic Triterpene, Chemosensitizes Human Tumor Cells through Inhibition of Nuclear Factor-κB Signaling Pathway - Harikumar, Kuzhuvelil B. (The American Society for Pharmacology and Experimental Therapeutics, 2010)
Agents that can enhance tumor cell apoptosis and inhibit invasion have potential for the treatment of cancer. Here, we report the identification of escin, a pentacyclic triterpenoid from horse chestnut that exhibits antitumor potential against leukemia and multiple myeloma. Whether examined by esterase staining, phosphatidyl-serine staining, DNA breakage, or caspase-mediated poly(ADP-ribose) polymerase cleavage, escin potentiated tumor necrosis factor (TNF)-induced apoptosis but inhibited tumor cell invasion. This correlated with the down-regulation of bcl-2, cellular inhibitor of apoptosis protein-2, cyclin D1, cyclooxygenase-2, intercellular adhesion molecule-1, matrix metalloproteinase-9, and vascular endothelial growth factor, which are all regulated by the activation of the transcription factor NF-κB. When examined by electrophoretic mobility shift assay, the triterpenoid suppressed nuclear factor-κB (NF-κB) activation induced by TNF and other inflammatory agents, and this correlated with the inhibition of IκBα phosphorylation and degradation, inhibition of IκB kinase complex (IKK) activation, suppression of p65 phosphorylation and nuclear translocation, and abrogation of NF-κB-dependent reporter activity. Overall, our results demonstrate that escin inhibits activation of NF-κB through inhibition of IKK, leading to down-regulation of NF-κB-regulated cell survival and metastatic gene products and thus resulting in sensitization of cells to cytokines and chemotherapeutic agents.